Study of the Diversity of Pollution Control Plants with Potential as Phytoremediator Agents for Heavy Metals in the City of Surabaya - Akhmad Ferdiansyah; Mukhlishatul Munawaroh; Argus (Postgraduate, University of Mataram, 2026)
Surabaya City has a lot of problems with the environment because of excessive urbanization and industrial activities, which include soil, air and water pollution. Among the pollutants of particular concern is heavy metal pollution. One method that can be tried in environmental remediation is phytoremediation, which is the use of plants to restore the environment. The present study focuses on identifying plants in Surabaya that have the capacity to function as heavy metal phytoremediation agents. The present study employs a purposive sampling method in conjunction with a line transect method. The results indicate that 34 plant species possess the capacity to function as effective heavy metal phytoremediation agents. A comprehensive review of the extant literature revealed ten types of heavy metal pollutants with the potential to be accumulated by heavy metal phytoremediation plants in the city of Surabaya, namely Pb, Hg, Cu, As, Fe, Al, Cr, Cd, Zn, and Ni. The diversity index (H') of 2.628, categorized as moderate, and the evenness index of 0.745, categorized as high evenness, indicate that the optimization of phytoremediation plant use can still be maximized by implementing sustainable planting activities as an effective strategy in controlling environmental pollution in large cities such as Surabaya.